Komodifikasi Progresif melalui Pendidikan Literasi Berbasis Kitab Kuning di Desa Tarokan Banyuanyar - Moh. Hasan Khoirul Anwar; M. Dzulkifli Nurul Huda (Najah: Journal of Research and Community Service, 2026)
Study this to find out. 1. The process of developing the pesanteren curriculum in developing the book of yellow. 2. The obstacles and support for the growth of the boarding school in the nuriddahlan boarding house. PKM has been using abcd approach with an improved design reading the Yellow Book. The research site is from a boarding house in nuriddahlan with banyuanyar. From the results of community inbreeding, there are several findings. First, performance of the boarding curriculum in full support by boarding, the boarding curriculum in developing a book of yellow which this activity is supported by boarding school because it increases the potential of students at nuriddahlan boarding school. By reviewing the books of the ancient scriptures adapted to material on the islamic religious education curriculum, the results are better because of using the original source of the Yellow Book, fiqih USES the book of taqrib, use the washoya and so on. After a review can be deduced that the Yellow Book's contribution to the development of the islamic religious education curriculum is strongly dominant.